Politik Identitas dalam Budaya Indonesia/Melayu - David T Hill (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2006)
In addition to looking into the socio-political milieu of the production and interpretation of Indonesian literature, as well as the historic interaction between some Indonesian and Malay writers, this article also attempts to discuss changes in the meaning of ‘Malay’ identity and ‘Malayness’ and the application of certain interpretations of such an identity in both the contemporary and historic perspectives. The discussion depends largely on Joel Kahn’s anthropological analysis of ‘nationalism and cosmopolitanism in Modern Malay world. ‘A comparison with the meaning and application of ‘Indonesia’ identity will then be made. Some conclusions that can be drawn are, among others, that the malayness/indonesianess’ of a writer is not relevant since literature as a text is not based on the ethnic category to which the writer belongs, but on its language or its milieu of production. However, it is also realized that this analysis may be too simplistic as it does not take into account the many exceptions that exist. Finally, this article does not aim to offer any solution to the indeterminacy surrounding the ‘Malay’ or ‘Indonesia’ identity in this global era, and at best, it can only bring up a set of questions for our contemplation.